2019
DOI: 10.36387/jiis.v4i1.257
|View full text |Cite
|
Sign up to set email alerts
|

POTENSI ANTIOKSIDAN DARI EKSTRAK KULIT BATANG Bauhinia semibifida Roxb

Abstract: Telah dilakukan penelitian tentang uji aktivitas antioksidan ekstrak kulit batang pohon kupu-kupu (Bauhinia semibifida Roxb) dengan metode DPPH. Pengujian aktivitas antioksidan menggunakan ekstrak n-heksana, etil asetat dan metanol dari kulit batang pohon kupu-kupu dan sebagai kontrol pembanding digunakan Vitamin C. Pengujian berdasarkan absorban DPPH terhadap ekstrak pada panjang gelombang 517 nm menggunakan microplate reader. Hasil penelitian menunjukkan bahwa ekstrak n-heksana kulit batang pohon kupu-kupu m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 1 publication
0
3
0
2
Order By: Relevance
“…In this study the antioxidant activity assay showed that the IC50 values for the ethanol and methanol extracts were 370.26 ppm and 318.85 ppm, respectively, classifying their antioxidant activity within the weak category. Conversely, vitamin C demonstrated a remarkably low IC50 value of 42.0, indicating a significantly potent antioxidant activity in the very strong category [28]. The observed weak antioxidant activity of the binahong leaf extracts could potentially be attributed to the extraction methodology used.…”
Section: Antioxidant Activity Testmentioning
confidence: 95%
See 1 more Smart Citation
“…In this study the antioxidant activity assay showed that the IC50 values for the ethanol and methanol extracts were 370.26 ppm and 318.85 ppm, respectively, classifying their antioxidant activity within the weak category. Conversely, vitamin C demonstrated a remarkably low IC50 value of 42.0, indicating a significantly potent antioxidant activity in the very strong category [28]. The observed weak antioxidant activity of the binahong leaf extracts could potentially be attributed to the extraction methodology used.…”
Section: Antioxidant Activity Testmentioning
confidence: 95%
“…The degree of antioxidant potency is quantitatively expressed as the Inhibitory Concentration (IC50) value, which indicates the concentration of the extract required to inhibit 50% of the DPPH radicals or its ability to reduce free radicals by 50%. A lower IC50 value indicates higher antioxidant activity, suggesting the extract's effectiveness in neutralizing free radicals and, consequently, its potential to mitigate oxidative stress and associated health benefits [27], [28]. Antioxidant activity can be categorized into distinct levels of potency, namely: very strong (IC50 < 50 ppm), strong (IC50 between 50-100 ppm), moderate (IC50 between 100-150 ppm), weak (IC50 between 150-200 ppm), and very weak (IC50 > 200 ppm) [29].…”
Section: Antioxidant Activity Testmentioning
confidence: 99%
“…The DPPH scavenging activity assay was conducted following the method mentioned in Fadhli et al, (2019) with a slight modification, where, 11 concentration of standards were used instead of six standards. The ascorbic acid was used as a positive control in this experiment.…”
Section: Dpph Radical Scavenging Assaymentioning
confidence: 99%
“…diperoleh senyawa fenolik 6C-7O-dimethylaromadendrin dan phlorizin yang memiliki aktivitas sitotosik terhadap sel Murin Leukimia P-388 dengan IC50 sebesar 72,93 ppm. Selain itu, pada penelitian Fadhli et al (2019) menunjukkan bahwa ekstrak metanol kulit batang B. semibifida Roxb. memiliki aktivitas antioksidan yang kuat dengan nilai IC50 sebesar 16 µg/mL.…”
Section: Pendahuluanunclassified
“…Berdasarkan Tabel 1 dan gambar 1, senyawa murni BR2 dan BR3 memiliki aktivitas sangat kuat sebagai antioksidan dengan nilai IC50 sebesar 2,92 µg/mL dan 4,39 µg/mL dibandingkan pada penelitian sebelumnya yang menunjukkan bahwa ekstrak metanol kulit batang B. semibifida Roxb. memiliki IC50 sebesar 16 µg/mL (Fadhli et al, 2019). Perbedaan aktivitas antioksidan senyawa BR2 dan BR3 yang merupakan senyawa murni dibanding dengan ekstrak metanol, dikarenakan ekstrak metanol mengandung lebih dari satu senyawa aktif yang memungkinkan adanya interaksi pada senyawa ekstrak tersebut, di mana interaksi bersifat antagonis ataupun sinergis (Prieto et al, 2014).…”
Section: Analisis Dataunclassified